The Role of Major Depressive Disorder and its Moderating Effect on the Impact of Exposure to Violence for Predicting Recidivism among Juvenile Offenders: A Survival Analysis Approach - Wojciechowski, Thomas (The prison journal, 2021)
Past research has indicated that Major Depressive Disorder and exposure to violence are risk factors for offending. However, researchers have yet to examine how this disorder may predict recidivism risk among juvenile offenders and how the disorder moderates the effect of exposure to violence. Kaplan-Meier survival analysis was used to determine the impact of Major Depressive Disorder on time to recidivism. Cox proportional hazard modeling was applied to examine Major Depressive Disorder as a moderator of exposure to violence. Results indicated that participants with Major Depressive Disorder demonstrate greater risk for recidivism post-adjudication. The proposed moderation effect was not supported.